If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 = 31 + -2(x + -1) Reorder the terms: 39 = 31 + -2(-1 + x) 39 = 31 + (-1 * -2 + x * -2) 39 = 31 + (2 + -2x) Combine like terms: 31 + 2 = 33 39 = 33 + -2x Solving 39 = 33 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 39 + 2x = 33 + -2x + 2x Combine like terms: -2x + 2x = 0 39 + 2x = 33 + 0 39 + 2x = 33 Add '-39' to each side of the equation. 39 + -39 + 2x = 33 + -39 Combine like terms: 39 + -39 = 0 0 + 2x = 33 + -39 2x = 33 + -39 Combine like terms: 33 + -39 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| -3-3z=3(-1-z) | | 3x+2+x-4=90 | | 5x+6-x=8+5x-5 | | 5x-8x+66=5x+26 | | -4=-3x-22 | | -4(5p+4)-32=2(4p+4) | | -8(r-4)=-1+3r | | 7d+14=10d+50 | | 6-(5x-13)=-4(x+3)-3x+2x | | 4x+2+x-4=90 | | 4t-15=12+13t | | 6y-2t= | | 8-6x=-3x-13 | | -p+6(2p-1)+3= | | 7x-4-3=0 | | SA=2(lw+hw+hl) | | v/6-2=-5 | | 4(w+5)=-2(5w-9)+6w | | -(9x+1)=80 | | 5(x+2)-5(y-3)-2x+5y= | | 15(4c-4)=5c-4 | | -p+5(2p-3)+5= | | -6t+4=40 | | 9x-36=2x+2 | | 36x^2+12x+144=0 | | 8r+3=4r-5 | | -1+6(-x-3)=-16-3x | | y^2-10y=-20 | | 2.455/0.125= | | 15(4c-4)=5c-5 | | -84=4(3-6r) | | -7-3z=8+2 |